Parenting for Liberation : A Guide for Raising Black Children - Brown, Trina Greene (Book collections on Project MUSE., 2020)
"Parenting for Liberation: A Guide for Raising Black Children is Trina Greene Browne's debut nonfiction work, and addresses the subject of how to raise Black children in a world of systemic racism, violence, and inequality. Pairing personal stories with open-ended prompts for reflection, this book serves as a support for people seeking to root their parenting techniques in practices of liberation"--